2017
DOI: 10.1371/journal.pone.0176084
|View full text |Cite
|
Sign up to set email alerts
|

The role of air pollution in myocardial remodeling

Abstract: BackgroundExcessive air pollution in urban environments can impact morbidity and mortality. The authors evaluated the role of particulate matter2.5 (PM2.5) in structural, geometric, and functional remodeling in hearts, using an experimental model of myocardial infarction.Methods and findingsSeventy-five rats were divided into 5 groups: control (CG), CG exposed to PM2.5 pollution (CGP), myocardial infarcted group (MI), infarcted group immediately exposed to pollution (IGP-I), and infarcted group previously expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
0
14
0
5
Order By: Relevance
“…A recent study has suggested that particulates act as adjuvants and promote long-lasting allergic inflammation in the airways 7 . Studies investigating the potential mechanisms underlying the adverse effects of exposure to PM2.5 have suggested that these include inflammation, oxidative stress, and apoptosis response 8 . Although some studies have investigated the effect of natural exposure to PM2.5 on the health of traffic policeman or employees at trucking terminals 9 , 10 , the precise mechanism/s linking the effects of PM2.5 pollution in real-life settings on human health have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has suggested that particulates act as adjuvants and promote long-lasting allergic inflammation in the airways 7 . Studies investigating the potential mechanisms underlying the adverse effects of exposure to PM2.5 have suggested that these include inflammation, oxidative stress, and apoptosis response 8 . Although some studies have investigated the effect of natural exposure to PM2.5 on the health of traffic policeman or employees at trucking terminals 9 , 10 , the precise mechanism/s linking the effects of PM2.5 pollution in real-life settings on human health have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The observed trend of increased left ventricular and atrial volumes may be a result of direct adverse cardiac remodeling and fibrosis stimulated by HAP. Studies in rats have previously documented the role of fine particulate matter (PM 2.5 ) in stimulating cardiac fibrosis [14,34].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies evaluating masked hypertension have shown an 8-20% prevalence in the general population and up to 50% prevalence in treated hypertensive patients, although the Nepali population has not been specifically studied [9,27]. It is also possible that prior studies have found an association with hypertension and HAP because such studies relied on field evaluations [5,14,16]. Transient blood pressure effects similar to "white coat" hypertension may have been attenuated in our study given that study participants had to travel to Pokhara for evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that the alternation of gene expression played a major role in the activation of pathways induced by toxicant exposure [20][21][22][23][24]. Recent studies indicated that PM 2.5 could enter cells via pinocytosis, and could alter the gene expression of lung epithelial and myocardial cells.…”
mentioning
confidence: 99%
“…Recent studies indicated that PM 2.5 could enter cells via pinocytosis, and could alter the gene expression of lung epithelial and myocardial cells. These alterations then inhibited cell apoptosis, induced cell proliferation and promoted angiogenesis, which are considered as indicators of tumor genesis [21,25]. Meanwhile, the chronic obstructive pulmonary disease (COPD) progress could also be accelerated, and even the mortality was increased by the short term PM 2.5 exposure [26].…”
mentioning
confidence: 99%